Investigation of electron-phonon interaction in bulk and nanostructured semiconductors - Yaremko, A.M.; Yukhymchuk, V.O.; Dzhagan, V.M.; Valakh, M.Ya.; Azhniuk, Yu.M.; Baran, J.; Ratajczak, H.; Drozd, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
In this paper, the problem of electron-phonon interaction (EPI) innsemiconductor crystals and quantum dots (QDs) is considered. It is shown that the model of strong EPI developed for organic molecular crystals can be successfully applied to bulk and nanosized semiconductors. The idea of the approach proposed here is to
describe the experimental Raman (or absorption) spectra containing the phonon replicas
theoretically by varying the EPI constant. The main parameter of the theoretical
expression describing the experimental spectrum is the ratio of EPI constant to the
frequency of the corresponding phonon mode. Based on the experimental and theoretical results, we have found that decreasing the size of CdSxSe₁₋x QDs embedded in borosilicate glass matrix results in some enhancement of electron-phonon interaction.